Association between Industry Payments and Scholarly Impact among Academic Ophthalmologists - Solotke, Michael; Forster, Susan; Chow, Jessica; Duran, Jenesis; Karim, Hasna; Marks, Victoria; Roy, Shireen; Torres, Ashlynn; Adelman, Ron (Journal of Academic Ophthalmology, 2019)
Purpose The aim of this article is to examine the association between industry payments to ophthalmologists and scholarly impact.Design Retrospective cross-sectional study.Methods All ophthalmology faculty at United States accredited ophthalmology residency programs were included in this study. The main exposure was industry payments to ophthalmologists in 2016, as reported in the Centers for Medicare and Medicaid Services Open Payments Database. The primary outcome was Hirsch index (H-index), a measure of scholarly impact.Results Among 1,653 academic ophthalmologists in our study, 1,225 (74%) received industry payments in 2016. We did not observe a difference between the mean H-index of ophthalmologists receiving any industry payments versus those not receiving any payments (p = 0.68). In analysis including only ophthalmologists who received industry payments, H-index differed significantly by payment amount: 12.6 for ophthalmologists receiving less than $100, 12.2 for those receiving $100 to 1,000, 18.8 for those receiving $1,000 to 10,000, 21.3 for those receiving $10,000 to 100,000, and 29.4 for those receiving greater than $100,000 (p < 0.001). Within each academic rank and gender, industry payments greater than $1,000 were associated with a higher H-index (p < 0.05).Conclusions Although our analysis cannot prove causality, we observed a significant association between industry payments and scholarly impact among academic ophthalmologists, even after adjusting for gender, academic rank, and subspecialty. Prospective studies should further evaluate this relationship.
Keywords: conflict of interest; health policy; industry payments